Strategi Optimalisasi Partisipasi Masyarakat Lokal dalam Pengelolaan Desa Wisata Brayut - Yuli Astuti, Dwi; Suyatno, Suyatno (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
This study aims to analyze strategies for optimizing community participation in the management of Brayut Tourism Village as part of local public governance to promote sustainability and improve the quality of tourism based on local wisdom. This study uses a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The results show that community participation is still dominated by certain groups, while other residents are less involved due to limited information, low awareness, inadequate skills, and communication barriers. Therefore, this study proposes a strategy for optimizing more inclusive and equitable participation through strengthening community capacity, organizing integrated training, providing information transparency, and developing two-way communication between the village government and the community. These findings have strategic implications for increasing accountability, transparency, and the effectiveness of tourism village governance as a form of participatory and sustainable public service. Optimal community participation not only strengthens tourism governance but also fosters a sense of ownership, expands the economy, and encourages adaptive and competitive village development. Strategic recommendations offered include increasing community capacity, utilizing information technology, strengthening two-way communication forums, developing multi-stakeholder collaboration, and implementing participation-based local regulations.